Effectiveness of Turmeric Decoke on Breast Milk Production for Postpartum Mothers - Rinda Lamdayani; Apriyanti Aini (GLOBAL HEALTH SCIENCE GROUP, 2025)
Every mother can breastfeed, but there are obstacles that hinder breastfeeding. Low exclusive breastfeeding rates can be influenced by several other factors such as socio-cultural, psychological, physical, health workers, knowledge, and family/community organization support. Compounds in turmeric are useful as a stimulus to facilitate the release of breast milk from the body so that breast milk will be quickly produced by the body through the performance of the hormone prolactin. The general objective of this study was to determine the effectiveness of turmeric decoction on breast milk production in postpartum mothers at PMB Sari Meryandi. This research method used Quasi-Experimental with a one-group pretest-posttest research design. Sampling was carried out using an accidental sampling technique with a total of 15 respondents.The sampling technique used was a questionnaire and an interview as the instrument. The population of this study was postpartum mothers on days 3-5 who were exclusively breastfeeding and experiencing irregular milk production. This study was conducted for 7 consecutive days by giving 100 grams of boiled turmeric water, followed by 200cc of water, to their babies, and drinking it either cold or warm. Smooth breastfeeding was categorized as having an average milk production of >50cc/24 hours.The data analysis used was the Wilcoxon test (data with non-normal distribution). The results of the univariate analysis showed an average knowledge level in the intervention group. The results of the 2-tailed Sig value <0.05, which means there is a significant difference in the pre-test and post-test values after the administration of turmeric boiled water in the intervention group.